Too Smart: How Digital Capitalism Is Extracting Data, Controlling Our Lives, and Taking over the World: Edited by Jathan SadowskiCambridge, MA: MIT Press, 2020. - Burns, Ryan (Economic Geography, 2021)
Often, critical scholars of digital technologies are most challenged in convincing I other scholars i of their deleterious impacts on knowledge production and sociopolitical inequalities. Even scholars who are otherwise critical of neoliberal capitalism are sometimes hard pressed to accept that I smart cities i are neither the inevitable future nor, under most conceptualizations, even a desirable future.